DARE Newsletter, Vol. 20, No. 1, Fall 2017 - DARE; Gardner, Elizabeth; Goebel, George (Dictionary of American Regional English, 2017)
Contents: "The News from DARE" by George Goebel; "In Memoriam: Patt VanDyke" by Elizabeth Gardner; "Contributors to DARE in 2016 and 2017"; "Linguistics Symposium Photos"; "Staff Member Profile: Yuhong (Jake) Zhu"; "A Word of Thanks"; " 'Words Count' Exhibition Photos"
Quarterly newsletter of the Dictionary of American Regional English
Keywords: Americanisms; Dictionaries; Lexicography; Regional English; English Language--Dialects--United States